Development of (TiB + TiN)/Ti composites via selective laser melting - Koh, Benjamin Jia Yuan (Nanyang Technological University, 2020)
Particle-reinforced titanium matrix composites have undergone a transition in their application with growing interest in aerospace, automotive and biomedical sectors due to their innate mechanical properties of high strength, wear resistance and good biocompatibility. In this study, the (TiB + TiN)-reinforced titanium matrix composites were in situ fabricated via selective laser melting. The formula of BN and Ti powders for the printed composites was optimized, and then the effects of process parameters on the microstructure and mechanical properties of (TiB + TiN)/Ti composites were investigated. Composite powders of the BN contents of 0, 0.5, 1, 2 and 3 wt% were prepared through mechanical blending after which the powder morphology, phase identification, microstructural features and mechanical properties were analysed. The results showed that whisker-like TiB and granular TiN were in situ formed during SLM. The tensile strength and microhardness of the titanium matrix were significantly improved with the addition of 0.5 wt% BN from 592.87 MPa to 1100.03 MPa and 172.74 HV to 315.64 HV respectively. The process optimization exhibited a wide processing window for the (TiB + TiN)/Ti composites with similar mechanical properties, indicating the greater sensitivity of composition to mechanical properties than process parameters. Fractography of the composites shown a transition of ductile fracture to brittle fracture with the addition of the BN reinforcement.